Application of the Econoland Game on Economic Actors Material to Increase Student Learning Activities in Economics Subjects - Siti Saodah; Gingin Ginanjar (FITK UIN Walisongo Semarang, 2023)
Based on the research findings that have been conducted, there is significant evidence of increasing student learning activities in the context of implementing the Econoland Game. The research results showed that the first cycle experienced an increase of 62%, while the second cycle showed a greater increase, namely 82.85%. From these results, it can be concluded that the application of the Econoland Game has proven effective in increasing student learning activities, as time goes by and the use of the game increases. In addition, these findings also highlight the importance of enjoyable learning in an educational context, as it was found that students' learning motivation levels also increased significantly. Thus, this research provides a valuable contribution in understanding the importance of innovative and more entertaining learning approaches in improving student learning outcomes and motivation in educational environments.